Single-Stage Extensor Digitorium Tendon Reconstruction, Including Overlying Soft Tissue Defects of the Foot Dorsum with a Composite-Free Anterolateral Thigh Flap - Sơn, Trần Thiết; Phúc, Lê Hồng; Nghĩa, Phan Tuấn; Minh, Nguyễn Đinh; Tùng, Nguyễn Thanh; Tuấn, Nguyễn Ngọc; Tú, Lương Thanh (Journal of Reconstructive Microsurgery Open, 2023)
Background Loss of the extensor tendon with overlying soft tissue remains a complex reconstructive challenge. Successful reconstruction combines tendon repair with defect coverage by soft tissue flaps, meets the goals of approaching functionality, and achieves an esthetic result.Patients and Methods From June 2016 to June 2022, our center submitted six patients to a one-stage procedure correcting the extensor tendon and skin defect using a composite-free anterolateral thigh (ALT) flap with fascia lata (FL).Results The ALT skin paddle was from 10 × 8 cm to 26 × 13 cm, and all flaps included vascularized FL with an average of 12 × 9.5 cm, which was split and folded to reconstruct as a tendon. The extensor digitorium brevis tendon defects were reconstructed by fascia sheets in all patients. One patient had additional reconstruction of the extensor hallucis longus tendon. All the flaps survived completely, and no complication was reported. All patients received rehabilitation therapy starting in the third week postoperatively. The mean follow-up was 33.67 months (range, 10–60). The mean arc of ankle rotation between dorsiflexion and plantar flexion was 49.20 degrees (range, 40–55 degrees). After reconstruction, our patients showed good functional results, and these patients could walk, climb stairs, tiptoe again without support, and regular footwear could be worn.Conclusion A composite-free ALT flap with vascularized FL is a reasonable option for coverage of the extensor tendon and overlying soft tissue defects. It helps reduce the surgical risk and hospitalization time and provokes faster recovery and rehabilitation.Level of Clinical Evidence Case studies, Level 4.
Keywords: anterolateral thigh flap; fascia lata flap; foot dorsum; extensor tendon defects; soft tissue defect